Pengembangan Kecerdasan Buatan Whatsapp Chatbot untuk Mahasiswa - Suryana, Ruly; Aryanto, Mukhlis; Kurniawan, Rizki; Satmata, Kyash Sabda Gusti Prabu; Yulianti, Yulianti; Saifudin, Aries (Program Studi Teknik Informatika Universitas Pamulang, 2022)
A chatbot is an artificial intelligence-based computer program that can carry out conversations via audio or text. This study intends to identify and analyze the types of artificial intelligence in the form of chatbots and their possible use as chatbot-based communication media. Currently, the practice in most is that branch employees need to consult with the central employees or search through official websites for work-related information. However, the process of obtaining the required information can take some time ranging from minutes to hours and is sometimes inconsistent as questions are answered by different employee members. There are WhatsApp chat groups for branch employees to interact with central employees, but group chats can be overwhelmed by questions due to the large number of members causing important messages to be ignored. In an effort to overcome this challenge, we developed a WhatsApp chatbot to overcome this problem by offering a centralized platform of communication for central employees and branch employees to share information via WhatsApp messages. Communication in the form of personalized messages between chatbots and users thus solving the overwhelming messaging problem that group chats pose. The Agile Kanban methodology was used to develop a system that promotes the use of Kanban boards to visualize development stages. A questionnaire is distributed to branch employees, head office employees and managers to test the system and collect opinions and suggestions from target users to assess whether the system is meeting its objectives. The biggest benefit of the Kanban methodology is the ability to continuously improve work. It can be used in any work environment and is great in situations where work arrives unexpectedly.